Teacher training and distance education in the state of São Paulo, Brazil: an analysis of production (2000-2010) - José Rubens Lima Jardilino; Marcelo Donizete da Silva (Acta Scientiarum. Education, 2015)
This article analyzes the theses and dissertations produced at the three public universities of the state of São Paulo: USP, UNICAMP and UNESP, from 2000 to 2010. It focuses on the theme of teacher training in the production on Distance Education. Since the policies of the State for distance higher education have been primarily aimed at undergraduate courses, the manner how theses and dissertations have addressed this issue is discussed. The methodology used in this sampling consists of the same state-of-the-art or knowledge of the field of educational research. Results indicated a strong presence of the theme of Teacher Training in the analyzed production, with a redirection of focus to other peculiarities of formation that are neither centered on the teacher nor directed to his or her practice and career.